Small extracellular vesicles derived from umbilical cord mesenchymal stem cells alleviate radiation-induced cardiac organoid injury - Hu Cao; Liang Yue; Jingyuan Shao; Fanxuan Kong; Shenghua Liu; Hongyu Huai; Zhichao He; Zhuang Mao; Yuefeng Yang; Yingxia Tan; Hua Wang (Stem Cell Research & Therapy)
Abstract Background Radiation-induced heart disease (RIHD) is one of the most serious complications of radiation therapy (RT) for thoracic tumors, and new interventions are needed for its prevention and treatment. Small extracellular vesicles (sEVs) from stem cells have attracted much attention due to their ability to repair injury. However, the role of umbilical cord mesenchymal stem cell (UCMSC)-derived sEVs in protecting cardiac organoids from radiation-induced injury and the underlying mechanisms are largely unknown. Methods A radiation-induced cardiac organoid injury model was established by using X-ray radiation, and the optimal radiation dose of 20 Gy was determined by live/dead staining. After radiation, the cardiac organoids were treated with sEVs derived from UCMSCs, and energy metabolism, calcium transient changes and the ultrastructure of the organoids were assessed through Seahorse analysis, optical mapping and transmission electron microscopy, respectively. Confocal microscopy was used to observe the changes in mitochondrial ROS and mitochondrial membrane potential (ΔΨm). Furthermore, real-time quantitative PCR was used to verify the RNA-seq results. Results After X-ray radiation, the mortality of cardiac organoids significantly increased, energy metabolism decreased, and calcium transients changed. We also observed that the mitochondrial structure of cardiac organoids was disrupted and that ΔΨm was decreased. These effects could be inhibited by sEVs treatment. sEVs may protect against radiation-induced cardiac organoid injury by regulating oxidative phosphorylation and the p53 signaling pathway. Conclusion sEVs derived from UCMSCs can be used as a potential therapeutic strategy for radiation-induced heart disease. Graphical Abstract